An economic analysis of oil palms production in Malaysia using ARDL model / Mohammad Faisal Ridzuan - Ridzuan, Mohammad Faisal (Faculty of Plantation and Agrotechnology, 2018)
Demand for oils has been growing strongly since the last decade due to increase in global population and oils consumption. Palm oil also is one of the most important oils in the world and each year million tons of palm oil has been traded globally to be consumed by million people around the world. Malaysia is the second largest producer of palm oil after Indonesia and become the most important industry in growth and development of Malaysia economic. Regarding the matter, the aim of the study is to investigate the impact that drive the Fresh Fruit Bunch (FFB) yield production and to review the relationship between oil palm productions, prices of crude palm oil, price of soybean oil and planted area of oil palms that causes increase or decrease oil palm productions in Malaysia by applying Autoregressive Distributed Lags (ARDL) model. In this study, the data were collected from MPOB, Index Mundi and Department of Statistic (Malaysia) from period 1995 until 2016. The method used to identify the short-run and log-run production analysis oil palms production in Malaysia. The finding of the study illustrate that real CPO prices, soybean oil prices and planted area palm oil are statistically significant with oil palm production for Malaysia in long-run and short-run able to readjust about 0.00104% to long-run equilibrium. This clearly point out to the fact that Malaysia is strong in exporting of palm oil and looking the value, there is has a great potential and strengthen in the palm oil industry. The study gives benefits to the several areas of the research. Thus, from this study it can helps several industry and government such as FELDA, FELCRA, MPOC, MPOB, MOF to understand the current challenges of oil palm industry due to competitiveness in the world market and to improve their productivity in palm oil industry.